Apply the product rule to <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>a</mi></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>16</mn></mstyle></math> .

Rewrite <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> as <math><mstyle displaystyle="true"><msup><mrow><mn>2</mn></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Factor out <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Move <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Rewrite <math><mstyle displaystyle="true"><msup><mrow><mn>2</mn></mrow><mrow><mn>3</mn></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> as <math><mstyle displaystyle="true"><msup><mrow><mo>(</mo><mn>2</mn><mi>a</mi><mo>)</mo></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Add parentheses.

Pull terms out from under the radical.

Do you know how to Simplify cube root of (-2a)^4? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.